Supplementation with protected fat to manage gastro-intestinal nematode infections in Santa Ines sheep - Afonso, Vivian Alves Costa; Costa, Ricardo Lopes Dias; Soares Filho, Cecilio Viega [UNESP]; Da Cunha, Eduardo Antonio; Perri, Silvia Helena Venturoli [UNESP]; Bonello, Fábio Luiz (My University, 2013)
This experiment aimed to determine the influence of supplementation with protected fat on nematode infections in periparturient sheep or sheep in their final stage of pregnancy. Fifty Santa Ines ewes received 200 g of concentrate/animal/day, mineral salt and water and were grouped according to their weight, hematocrit and the number of eggs per gram of feces (EPG). Two diets were used: a control treatment and a treatment consisting of supplementation with 30 g/animal/day of protected fat in the concentrate. Three monthly evaluations were performed over a total of 84 days of testing. The variables analyzed were weight, body condition, EPG and coprocultures; blood tests were performed for the determination of packed cell volume, hemoglobin concentration and total plasma protein, and leukograms and eosinophil counts were performed. For weight and hemoglobin concentrations, interactions were observed between diet and collection date (P<0.05); body condition, total plasma protein, packed cell volume and total leukocytes did not differ statistically among treatments (P> 0. 05) but did differ by collection day (P <0.05). The EPG and eosinophil counts did not differ statistically by either diet or collection date (P>0.05). The genus Haemonchus was predominant, followed by the genera Cooperia, Trichostrongylus and Oesophagostomum. The protected fat did not decrease EPG and did not improve the blood parameters of infected sheep.
Keywords: Haemonchus; Nutrition; Polyunsaturated fatty acids; Sheep